Features of Fatigue Cracks in Gears and Diagnosis Methods - 张桂才; 赵万镒; 沈玉娣; 屠荣富 (Jixie chuandong)
In this paper, features of fatigue cracks in ge.ars and diagnosis methods are studied. Multiple methods are compositely used for analyzing the vibration signals of the gearbox. The crack on gear tooth is successfully recognized.